KARL JASPERS'IN FELSEFESİNDE İNSANIN VAROLUŞUNU GERÇEKLEŞTİRMESİ OLARAK İLETİŞİM - H.haluk Erdem (Felsefe Dünyası)
The question "What is humanbeing?" is one of fundamental questions in philosophy of Jaspers. According to Jaspers, humanbeing is a being that is essentially more than what he knows and what is known about himself. The essential being of man is his existence. Existential communication existentielle Kommunikation is a sign signa realizing the possibility of man's existence. The properties of the existential communication are man's creative loneliness and creative independence, being open to the other, responsibility for the other, and acceptance of the other as being equal to himself. In Jaspers' view of existential communication man is not an instrument but an aim.